Effects of Seasonal and Perennial Climatic Fluctuations on Geographical Distribution of the Enhanced Vegetation Index EVI of Arable Land in the Bryansk Region - LOBANOV, Grigory V.; AVRAMENKO, Marina V.; CHAROCHKINA, Anna Yu.; DROZDOV, Nikolay N. (Journal of Environmental Management and Tourism, 2019)
This article discusses the patterns of geographical distribution of the enhanced vegetation index EVI within the Bryansk region (upper Dnieper basin, south-western Russia) in the spring months of 2010-2015. The factors of index distribution, based on agricultural land monitoring data in other regions, are described. The crucial role of abiotic (topography, soil) and biotic factors in the distribution of the EVI is shown. The generalized data of meteorological observations of 2010-2015 are presented; the effects of their high variability on the range of the EVI values and its geographical distribution are shown. Data on the differences in the EVI distribution in the spring months of 2010-2015 is presented, which are explained by the differing periods of phenological seasons, surface relief characteristics (flat and convex watersheds, drainage conditions), lithological composition and humus content in the upper horizons of arable soil. A qualitative relationship between spring changes in the EVI for arable land and the combination of edaphic factors of agro-landscape functioning is established and the mechanisms that ensure such differences are presented. The use of the EVI distribution patterns is justified in the years with different climatic conditions to identify arable lands with different surface topography and soil characteristics.